2019
DOI: 10.1109/access.2019.2954672
|View full text |Cite
|
Sign up to set email alerts
|

A New Secure Encryption Scheme Based on Group Factorization Problem

Abstract: As special types of factorization of finite groups, logarithmic signatures and covers have been used as the main components of cryptographic keys for secret key cryptosystems such as PGM and public key cryptosystems like MST 1 , MST 2 , MST 3 and eMST 3. In particular, as a natural analogue of integer factorization problem (IFP), group factorization problem (GFP) and its hardness assumption over certain factorization basis, referred as logarithmic signature, play a core role in the security arguments for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
5
0
4
Order By: Relevance
“…У 2009 р. Lempken та інші описали криптосистему з відкритим ключем MST3, засновану на логарифмічному підписі та 2-групі Сузукі [7]. Криптосистеми на неабелевих групах та їх властивості активно вивчались в [8,9]. У 2010 р. Сваба та інші [10] проаналізували всі відомі атаки на криптографію MST і створили більш безпечну криптосистему eMST3, включивши секретне гомоморфне накриття.…”
Section: вступunclassified
See 2 more Smart Citations
“…У 2009 р. Lempken та інші описали криптосистему з відкритим ключем MST3, засновану на логарифмічному підписі та 2-групі Сузукі [7]. Криптосистеми на неабелевих групах та їх властивості активно вивчались в [8,9]. У 2010 р. Сваба та інші [10] проаналізували всі відомі атаки на криптографію MST і створили більш безпечну криптосистему eMST3, включивши секретне гомоморфне накриття.…”
Section: вступunclassified
“…, ,..., ( , ) 17 , α 16 α 25 , α 17 , α 23 , α 27 α 13 , α 0 , α 28 , α 10 α 13 , α 0 , α 28 , α 10 α 30 ,α 2 ,α 17 ,α 2 α 6 , α 7 , α 30 , α 18 α 9 ,α 4 ,α 9 ,α 20 α 9 ,α 4 ,α 9 ,α 20 α 14 , α 28 , α 17 , α 22 α 26 , α 5 , α 16 , α 30 α 12 , α 15 , α 17 , α 6 α 12 , α 15 , α 17 , α 6 α 22 , α 30 , α 22 , α α 24 , α 29 , α 15 , α α 3 ,0,α 14 ,α 9 Зворотні елементи ( ) ( )…”
Section: практичні обчисленняunclassified
See 1 more Smart Citation
“…Factoring a finite abelian group into subsets was first initiated by Hajós [8] to solve a famous geometry problem by H. Minkowski in 1941. In the past few decades, study of group factorization has received numerous research attentions (see [9,12]) and they found its applications in various field such as geometry of tiling, code theory, cryptography, graph theory and etc (see [5,6]). The current research has renew focused on factoring nonabelian groups into subsets (see [1,11]).…”
Section: Introductionmentioning
confidence: 99%
“…Більшість атак може буде імплементовано з використанням доступних обчислювачів. Водночас саме розуміння архітектури атаки стимулює спроби використання інших підходів до забезпечення потрібного рівня безпеки, на кшталт використання гомоморфного шифрування у якості додаткового елемента посилення конструкції[14], використання посилених логарифмічних підписів[15]. В останні роки, використовуючи обґрунтовані властивості неабелевих груп[16], результати робіт з пошуку кращих за характеристиками логарифмічних підписів[17], дослідникам вдалось запропонувати посилені конструкції Hard problems for non-abelian cryptography // 2021: Fifth International Scientific and Technical Conference "COMPUTER AND INFORMATION SYSTEMS AND TECHNOLOGIES", 2021, pp39-40, https://doi.org/10.30837/csitic52021232176 2.…”
unclassified